ROW SPACING AND IRRIGATION EFFECT ON RADIATION USE EFFICIENCY OF WINTER WHEAT - W. W. Zhong; J. Q. Liu; X. B. Zhou; Y. H. Chen; J. J. Bi (Journal of Animal and Plant Sciences, 2015)
Winter wheat is an important food crop in northern China. To achieving higher yields with less water has been the focus of researchers. Four planting patterns [row spacing (RS) × plant spacing], namely, 7 × 7 cm (RS7), 14 × 3.5 cm (RS14), 24.5 × 2 cm (RS24.5), and 49 × 1 cm (RS49), and four irrigation regimes, namely, 0, 60, 120, and 180 mm, were studied under field conditions during 2006–07 and 2007–08 at the Agronomy Experimental Station (36°09′N, 117°09′E) of Shandong Agricultural University in Tai′an, Shandong Province, China. This experiment aimed to study the effect of row spacing and irrigation on leaf area index (LAI), dry matter weight (DM), photosynthetically active radiation (PAR) capture ratio at different levels above the ground surface, grain yield and radiation use efficiency (RUE) of winter wheat. Results revealed higher average LAI and DM of RS14 than those of other treatments with all irrigation conditions. The canopy light interception of RS49 was significantly lower than those of other patterns. The PAR capture ratio of RS14 at 0–40 cm aboveground was lower than that at 40–80 cm aboveground, similar to those of RS7 and RS24.5 but not to that of RS49. Increased irrigation resulted in declines of PAR capture ratio at 0–40 cm aboveground but increased at 60–80 cm aboveground. Increasing amounts of irrigation resulted in increased yields of winter wheat, and the order RS14 ≈ RS7 > RS24.5 > RS49 was observed. Grain yields of RS7 and RS14 were significantly higher than those of RS24.5 and RS49 (P < 0.01). RS14 with irrigation at 120 mm may be the best option to increase yields and save water in northern China.
Keywords: Triticumaestivum L.; planting pattern; leaf area index; photosynthesis active radiation; grain yield